Penyelamatan Arsip Keluarga Melalui Layanan Arsip Keluarga (LASIGA) Pada Kelurahan Kwitang Jakarta - Lolytasari, Lolytasari; Ashri, Najmi Kurnia; Az Zahra, Fathimah; Hamidah, Mila; Wardani, Maharsi Dyah Kusuma; Suprayogi, Mukmin (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2025)
Background of the Study: The loss of archives leads to the disappearance of valuable recorded information. Family archives serve as crucial assets tied to identity, legal evidence, and property ownership. The Provincial Archival Institution plays a key role in educating the public and providing facilities for archive preservation. One such initiative is LASIGA, a family archive preservation program by the Jakarta Provincial Library and Archives Office (DISPUSIP). Objectives: This research aimed to analyze the implementation of the LASIGA program in Kwitang, North Jakarta. It examined DISPUSIP’s role in promoting awareness and engagement in family archive preservation. Method: A descriptive qualitative approach was used, involving three informants directly participating in LASIGA activities. Data collection included observations and documentation, followed by analysis to assess the program's effectiveness. Finding: The study found that DISPUSIP actively conducted outreach programs across Jakarta, educating the public on the significance of family archives. These initiatives emphasized archives as personal and national assets, successfully encouraging public participation in digitization efforts. The LASIGA program fostered enthusiasm among residents to preserve their records, reflecting the Jakarta government's commitment to archive conservation. Conclusion: The LASIGA program effectively increased public awareness of family archive preservation. Through educational outreach and facilitation, DISPUSIP successfully promoted the importance of safeguarding historical and legal documents for future generations.